Liraglutide ameliorates TAC-induced cardiac hypertrophy and heart failure by upregulating expression level of ANP expression - Ruisha Li; Keyin Zhang; Zhenjun Xu; Yanrong Yu; Dongjin Wang; Kai Li; Wenxue Liu; Jun Pan (Heliyon, 2024)
Recent studies have underscored the cardioprotective properties of liraglutide. This research explores its impact on cardiac hypertrophy and heart failure following transverse aortic constriction (TAC). We found that liraglutide administration markedly ameliorated cardiac hypertrophy, fibrosis, and function. These benefits correlated with increased ANP expression and reduced activity in the calcineurin A/NFATc3 signaling pathway. Moreover, liraglutide mitigated ER stress and cardiomyocyte apoptosis, and enhanced autophagy. Notably, the positive effects of liraglutide diminished when co-administered with A71915, an ANP inhibitor, suggesting that ANP upregulation is critical to its cardioprotective mechanism.